Relationship between velocity at anaerobic threshold and factors affecting velocity at anaerobic threshold in elite distance runners - Tjelta, L. I.; Rønning Tjelta, A.; Dyrstad, S. M. (International Journal of Applied Sports Sciences, 2012)
The purpose of the present study is to describe the relationships between running velocity at anaerobic threshold (vAT) and maximal oxygen uptake (VO2max), running economy (RE) and the fractional utilization of VO2max at vAT (%VO2max) in elite runners. vAT tests and VO2max tests were conducted on 34 Norwegian distance runners (22 males, 12 females) included in this study. Subjects completed between one and six tests each. The vAT test was assessed by treadmill running using a stepwise incremental protocol. vAT was defined as the running pace where blood lactate concentration [La-] was 1.5 mmol/L above warm up value. RE was set to be VO2 ml/kg/km. Standard multiple regression analysis showed that 89% of vAT could be predicted by VO2max, RE and % VO2max (n=34). There were, however, no significant correlations between vAT and any of the variables VO2max, RE and % VO2max in women, while VO2max was significantly correlated with vAT in men. This study indicates that in a group of elite runners, VO2max is the variable that most affects vAT among men. Among women, rather surprisingly, no significant correlations between vAT and any of the variables: VO2max, RE and % VO2max were found. This might be explained by large individual differences that to a certain extent equalize each other.